Spectral libraries from nucleobases and deoxyribonucleosides facilitate the identification of ribonucleosides by nano-flow liquid chromatography-tandem mass spectrometry - Espadas, Guadalupe; Llovera, Laia; Ollivier, Alexane; Tuorto, Francesca; Novoa, Eva Maria; Sabidó, Eduard (Rapid communications in mass spectrometry, 2024)
Rationale The study addresses the challenge of identifying RNA post-transcriptional modifications when commercial standards are not available to generate reference spectral libraries. It proposes employing homologous nucleobases and deoxyribonucleosides as alternative reference spectral libraries to aid in identifying modified ribonucleosides and distinguishing them from their positional isomers when the standards are unavailable. Methods Complete sets of ribonucleoside, deoxyribonucleoside and nucleobase standards were analyzed using high-performance nano-flow liquid chromatography coupled to an Orbitrap Eclipse Tribrid mass spectrometer. Spectral libraries were constructed from homologous nucleobases and deoxyribonucleosides using targeted MS2 and neutral-loss-triggered MS3 methods, and collision energies were optimized. The feasibility of using these libraries for identifying modified ribonucleosides and their positional isomers was assessed through comparison of spectral fragmentation patterns. Results Our analysis reveals that both MS2 and neutral-loss-triggered MS3 methods yielded rich spectra with similar fragmentation patterns across ribonucleosides, deoxyribonucleosides and nucleobases. Moreover, we demonstrate that spectra from nucleobases and deoxyribonucleosides, generated at optimized collision energies, exhibited sufficient similarity to those of modified ribonucleosides to enable their use as reference spectra for accurate identification of positional isomers within ribonucleoside families. Conclusions The study demonstrates the efficacy of utilizing homologous nucleobases and deoxyribonucleosides as interchangeable reference spectral libraries for identifying modified ribonucleosides and their positional isomers. This approach offers a valuable solution for overcoming limitations posed by the unavailability of commercial standards, enhancing the analysis of RNA post-transcriptional modifications via mass spectrometry.